Someday, maybe ebook - Nwabineli, Onyi (2022)
A GOOD MORNING AMERICA BOOK CLUB PICK • A BOOK OF THE MONTH CLUB PICK A LIBRARYREADS PICK "If you are someone who gravitates toward emotional gut punch reads, allow me to introduce you to this spectacular debut..."—BuzzFeed Here are three things you should know about my husband: He was the great love of my life despite his penchant for going incommunicado. He was, as far as I and everyone else could tell, perfectly happy. Which is significant because... On New Year's Eve, he died. And here is one thing you should know about me: I found him. Bonus fact: No. I am not okay. Someday, Maybe is a stunning, witty debut novel about a young woman's emotional journey through unimaginable loss, pulled along by her tight-knit Nigerian family, a posse of friends, and the love and laughter she shared with her husband. "Incisive and witty. I couldn't put it down."— Lolá Ákínmádé Åkerström , internationally bestselling author of In Every Mirror She's Black "A masterfully woven exposition on love and loss. Nwabineli is magic with words."—Bolu Babalola, internationally bestselling author of Honey and Spice Don't miss Onyi Nwabineli's next stunning page-turner, ALLOW ME TO INTRODUCE MYSELF, where a former kidfluencer must overcome her toxic family, reclaim her identity and, ultimately, find the freedom to be herself...